Atitude interdisciplinar, formador do professor e autonomia profissional - Ferreira, Nali Rosa Silva (2011)
The present work is about a formation-research which is carried out under the theoretical-methodological principles of interdisciplinary thought. It also proposes reflections over the interdisciplinary stance of the teacher of the future elementary school teacher through professional autonomy. The aim is to understand which direction must be taken by the practice of the teacher‟s teacher in order to mediate the construction of the professional autonomy (specifically the new kind‟ of autonomy) of the future teacher of the early years of elementary school. In the search for a new meaning in the didactical-pedagogical action, we have observed the trajectory of its movements, connecting them with a given life story as well as with the meanings of the meaning circle of Pineau and the interdisciplinary categories of Fazenda. The path of the investigation takes into account the signals stemming from the self-governance and the self-construction of autonomy under the existential parameters of these days, shaped by an environment of knowledge with frequent assimilation of new data in the various situations which demand autonomous learning. We seek, furthermore, to explore, validate and make explicit the nature and the direction of the didactical action under the principles of an interdisciplinary educational practice. We use memory records of the practice of teaching in the universities, documental analysis, focal groups as well as the answers from a survey which has an opening for a qualitative analysis of the accounts produced by students of the Pedagogy course (UniBH). The experience of an interdisciplinary stance, with the interdisciplinary methodological backings, allows for the comprehension of limits, difficulties and possibilities in the mediating action of the teacher of the future teacher by learning the new kind‟ of autonomy